1997
DOI: 10.1128/aem.63.6.2306-2310.1997
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Butanol Production by Clostridium beijerinckii BA101 Grown in Semidefined P2 Medium Containing 6 Percent Maltodextrin or Glucose

Abstract: Dramatically elevated levels of butanol and acetone resulted in higher butanol and total solvent yields for hyperamylolytic Clostridium beijerinckii BA101 relative to the NCIMB 8052 parent strain grown in semidefined P2 medium containing either 6% glucose or STAR-DRI 5 maltodextrin. C. beijerinckii BA101 consistently produced on the order of 19 g of butanol per liter in 20-liter batch fermentations. This represents a greater than 100% increase in butanol concentration by the BA101 strain compared to the parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(78 citation statements)
references
References 16 publications
4
67
0
1
Order By: Relevance
“…In particular, on mannose, BA105 demonstrated significant amounts of solvent production over 20 g L À1 , that is similar to BA101 mutant well known for hyper-butanol producing strain. [7] Although glucokinase could be responsible for the phenotypic change of BA105, it is still unclear whether the mutation in the glucokinase gene of BA105 affected its regulatory function or the enzyme activity. A further study focusing on sugar transport needs to be performed to confirm the effect of the glucokinase mutation on sugar utilization in C. beijerinckii.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, on mannose, BA105 demonstrated significant amounts of solvent production over 20 g L À1 , that is similar to BA101 mutant well known for hyper-butanol producing strain. [7] Although glucokinase could be responsible for the phenotypic change of BA105, it is still unclear whether the mutation in the glucokinase gene of BA105 affected its regulatory function or the enzyme activity. A further study focusing on sugar transport needs to be performed to confirm the effect of the glucokinase mutation on sugar utilization in C. beijerinckii.…”
Section: Discussionmentioning
confidence: 99%
“…[3] However, the BA105 mutant has not been further characterized or used for butanol production, while the BA101 mutant that was developed at the same time has been widely studied and known as a hyper-solvent producing mutant. [3,[7][8][9][10] The previous study reported that the enhanced amylolytic activity correlated with higher butanol production in C. beijerinckii. [2,3] Therefore, we revisited BA105 mutant to test its potential ability to overproduce butanol in this study.…”
Section: Introductionmentioning
confidence: 99%
“…C. beijerinckii BA101 has an altered acid-to-solvent switching mechanism and produces butanol during the exponential phase (Formanek et al, 1997). Although the initial levels of acids produced by C. beijerinckii BA101 are similar to its parental strain, the levels decrease dramatically during solventogenesis.…”
Section: Beijerinckii Ba101 and Process Developmentmentioning
confidence: 99%
“…Many industrial strains have been generated by random mutation and subsequent selection. The C. beijerinckii BA101 strain was generated by treating C. beijerinckii NCIMB 8052 with a mutagen N-methyl-N9-nitro-N-nitrosoguanidine and selectively enriching the candidate mutants on the nonmetabolizable glucose analog 2-deoxyglucose (Formanek et al, 1997). C. beijerinckii BA101 is able to produce twofold more butanol and acetone than its parent strain and has distinct fermentation characteristics.…”
Section: Beijerinckii Ba101 and Process Developmentmentioning
confidence: 99%
“…During the last 40 years, fluctuations (both rise and fall) in gasoline prices encouraged researchers around the world to focus on the development of novel microbial strains and fermentation processes to make production of this biofuel economically viable. [1][2][3][4][5][6][7][8][9][10][11][12] Butanol can be produced from sugars such as glucose, sucrose, and lactose in a two step process (fermentation 1 distillative recovery). The microbial strains such as Clostridium beijerinckii, C. acetobutylicum, or C. saccharobutylicum can produce enzymes that hydrolyze disaccharide sugars (sucrose and lactose) into monomeric sugars followed by fermentation to butanol.…”
Section: Introductionmentioning
confidence: 99%